Association of HLA-DRB1/DQB1 Alleles and Genetic Susceptibility to Type 1 Diabetes Mellitus - Hussein, Hiba Omer AbdelRhman; Abdalla, Sababi Salih; Salih, Sakeena NourEldine; Abdrabo, AbdElkarim; Mahdi, Mohamed Abdelgadir (AL-Kindy College Medical Journal, 2023)
Objective: This study was conducted to identify the association of HLA-DRB1/DQB1 genes with the susceptibility or resistance to type 1 diabetes mellitus (T1D) among patients between the ages of five and eighteen. Subjects and Methods: The study included 200 Sudanese participants, ages ranging from 5 to 18. One hundred participants were healthy non-diabetic as the control group and 100 with T1D as the case group. The investigation was carried out in Khartoum state. The selection of patients with T1D was from diabetic centers and hospitals. The allele-specific-refractory mutation system-polymerase chain reaction (ARMS-PCR) technique was applied to identify the HLA gene polymorphism. Results: There was a significant difference in genotype frequency across the groups in the current investigation (Kruskal-Wallis, p-value= 0.021). Whereas CG was not substantially different across groups (Chi-square, p-value=0.116), the CC genotype was considerably greater (46.0%) in patients (Chi-square Adjusted p-value0.001). Conclusion: This study found that patients’ genotypes and allele frequencies are significantly correlated when compared to those of healthy participants.